2009
DOI: 10.1016/j.ejvs.2009.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Symptomatic and Asymptomatic Peripheral Arterial Disease and the Value of the Ankle-brachial Index to Stratify Cardiovascular Risk

Abstract: ABI<0.9 is relatively frequent in those 35-79, particularly over 74. However, IC and CHD risk> or =10% indicators are often missing. Adding ABI measurement to CHD-risk screening better identifies moderate-to-high cardiovascular risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
68
2
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(87 citation statements)
references
References 34 publications
10
68
2
7
Order By: Relevance
“…Of patients who attended an angiology office in Spain due to intermittent claudication and who underwent arterial surgery or had an ABI ≤ 0.9, 67% had diabetes mellitus [16] . Population-based studies in Spain, undertaken in either the general population or at various levels of care, showed that the presence of diabetes mellitus doubled or even tripled the possibility of having PAD (Table 1) [6, [17][18][19][20][21][22][23] . The prevalence of an ABI < 0.9 in series of Spanish patients with diabetes ranges from 21% to 60% (Table 1) [8, 24,25] .…”
Section: Diabetes and Padmentioning
confidence: 99%
“…Of patients who attended an angiology office in Spain due to intermittent claudication and who underwent arterial surgery or had an ABI ≤ 0.9, 67% had diabetes mellitus [16] . Population-based studies in Spain, undertaken in either the general population or at various levels of care, showed that the presence of diabetes mellitus doubled or even tripled the possibility of having PAD (Table 1) [6, [17][18][19][20][21][22][23] . The prevalence of an ABI < 0.9 in series of Spanish patients with diabetes ranges from 21% to 60% (Table 1) [8, 24,25] .…”
Section: Diabetes and Padmentioning
confidence: 99%
“…Our results are in agreement with those of Mourad et al [17] who studied a population of 2146 patients at high cardiovascular risk and found that 41% of them had ABI<0.9. Conversely, previous studies, which found lower PAD rates (30%), were performed in lower risk subjects such as patients hospitalized for nonvascular diseases or cardiovascular outpatients followed by general practitioners [10,18]. Our data show that asymptomatic PAD is widely diffuse in HF patients and highlight the utility of ABI as screening tool in such population.…”
Section: Discussionmentioning
confidence: 44%
“…The present study also confirmed that the male patients suffering from chronic venous insufficiency had higher ABI values (statistically significant) than the female patients. Similarly, the research conducted by Ramos et al (2,903 men and 3,269 women) confirmed that male patients with lower extremity arteriosclerosis had lower ABI values [11]. Finnish scientists reported some slight differences in this subject, too [12].…”
Section: Discussionmentioning
confidence: 59%